PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKUTURAL NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII.2 SMP NEGERI 5 TAMBANG - Aulia Bestari; Yenita Roza; Sakur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:This researches was a classroom action research which aims to improve the performance of teacher and improving the student mathematic achievement. This researches implemented the cooperative learning by using structure approach of numbered head together (NHT) at class VII.2 SMPN 5 Tambang academic year 2015/2016. This learning used identification number of students in order to increase the responsibility of students during the learning process. The data in this study consisted of the activity data on learning process and the data of student mathematic achievement. The activity data were collected by using teacher observation sheet and student observation sheets while the data of student mathematic achievement were collected by using test. These data were analyzed descriptively. The data analyzed showed that activities of students and teacher is getting better. The teacher done reflection after learning to improve the previous weakness. The student mathematic achievement increased by observing the achievement of KKM. The percentage of students who achieved KKM on cycle 1 was 54.16% and 75.00% in cycle 2. There was improvement of student mathematics achievement because the percentage of student who achieved KKM before action was only 33.33%. It can be concluded that the implementation of cooperative learning by using structure approach of numbered head together (NHT) can improve student mathematic achievement at class VII.2 SMPN 5 Tambang.KeyWord : Students’ Math Achievement, Cooperative Learning Model Structural Approach of Numbered Heads Together, Classroom Action Research.